LITERACY AND INCREASING STUDENTS' READING INTEREST: A CASE STUDY AT SUKMA BANGSA LHOKSEUMAWE SCHOOL, INDONESIA - Andi Mursalin; Saifuddin; Suadi Zainal; Dini Rizki (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This study examines the Application of School Literacy in increasing students' interest in reading. The main focus of this research is on the strategy of implementing literacy programs in schools and how it impacts the increase of students' interest in reading. This research was carried out at SMAS Sukma Bangsa Lhokseumawe. This research uses a qualitative method. Data collection techniques through observation, interviews and documentation. Data analysis is carried out through three stages, namely data reduction, data presentation, and conclusion drawn. This study uses Pierre Bourdieu's Habitus Theory. The results of the research concluded that the strategy for implementing literacy programs in schools is with a conditioning class with homeroom teachers for 30 minutes of literacy activities in the classroom. Meanwhile, the impact of literacy on increasing reading interest is increasing knowledge and reading interest is getting higher so that students are used to reading books and finding motivations in their reading books. The impact of literacy at Sukma Bangsa School in Lhokseumawe has been quite positive for students, as it has increased their interest in reading and writing. This literacy development extends beyond reading and writing habits, but students are also able to compete in writing competitions and youth scientific competitions. Theoretically, it can be said that the habitus of reading is a basic understanding or value born from the internalization of social structures built in the school environment.